On the Equivalence of Private and Public Money - Markus K. Brunnermeier; Dirk Niepelt (Center for Economic Studies and ifo Institute (CESifo), 2019)
When does a swap between private and public money leave the equilibrium allocation and price system unchanged? To answer this question, the paper sets up a generic model of money and liquidity which identifies sources of seignorage rents and liquidity bubbles. We derive sufficient conditions for equivalence and apply them in the context of the “Chicago Plan”, cryptocurrencies, the Indian de-monetization experiment, and Central Bank Digital Currency (CBDC). Our results imply that CBDC coupled with central bank pass-through funding need not imply a credit crunch nor undermine financial stability.
Keywords: E40; E50; G10; H60; 330; money creation; monetary system; inside money; outside money; equivalence; CBDC; Chicago Plan; sovereign money